Muscular sarcoidosis in the eyes of 18F‐FDG PET/CT. Issue 3 (24th December 2021) - Milojevic, Isidora Grozdic; Sobic‐Saranovic, Dragana; Milojevic, Bogomir; Artiko, Vera M.
Abstract: Purpose: The aim of this study was to determine the frequency, symptoms, activity and pattern of muscle sarcoidosis, correlation with laboratory parameters, and to assess its therapy response with 18 F‐FDG PET/CT. Methods: Study included 90 patients with biopsy confirmed sarcoidosis and symptoms/biochemical/imaging findings suggestive of active disease. The exclusion criteria were: presence of cancer or other diseases that resemble sarcoidosis on PET/CT (Wegener syndrome, tuberculosis, aspergillosis), and the glucose level being greater than 11 mmol/L. All patients were screened for muscle sarcoidosis with 18 F‐FDG PET/CT examination. Follow‐up examination was done 1 year after the baseline in order to evaluate therapy response. Results: Disease was very rare and present in only 7/90 patients. Most of the patients had polysymptomatic disease, while muscle pain was less frequent, present only in one‐third of the patients. The disease was usually present in the lower limbs, upper limbs, and skeletal striated muscles. The most common pattern of disease was nodular. Disease activity estimated with SUVmax was not in correlation with the ACE findings, creatine kinase, and aldolase levels ( p > 0.05). Follow‐up PET/CT revealed complete remission in one patient and partial remission in two. Conclusion: 18 F‐FDG PET/CT can be useful in asymptomatic young patients with nodular pattern of disease, who have easily relapsing form of disease. It can help in further management of these patients and can affect prognosis of the disease, since most of the laboratory parameters in this entity are within normal limits. Abstract : 18 F‐FDG PET/CT can be useful in the detection of muscular sarcoidosis, its pattern, and evaluation of the therapy response. It can help in further management of these patients and can affect prognosis of the disease.